One hundred poems from the chinese - Rexroth, Kenneth
The lyric poetry of Tú Fu ranks with the greatest in all world literature. Across the centuries - Tu Fu lived in the T ang Dynasty (713-770) - his poems come through to us with an immediacy that is breathtaking in Kenneth Rexroth s English versions. They are simple as they are profund, as delicate as they are powerful. Thirthy -five poems by Tu Fu make up the first part of this volume. The translator then moves on to the Sung Dynasty (10th-12th centuries) to give us a number of poets of that period, much of whose work was not previusly avaible in English: Mei Yao, C'hen, Su Tung P'o, Lu Yu, Chu Hsu Chao, and the poetesses Li Ch'ing Chao and Chu Shu Chen. There is general introduction, biographical and explanatory notes on the poets and poems, and a bibliography of other translations of Chinese poetry.